Mohammedan Temple. Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (My University, 2010)
Photo of mosque in St. James, Port of Spain, Trinidad and Tobago. Postcard number 52.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Mosques--Trinidad and Tobago; Islam--Trinidad and Tobago; Muslims--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--St. James; Architecture--Trinidad and Tobago; Architecture, Asian--Trinidad and Tobago; Islamic architecture--Trinidad and Tobago; Minarets--Trinidad and Tobago